2011
DOI: 10.1021/jp204799q
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Functionals Study of Band Bowing, Band Edges and Electronic Structures of Cd1–xZnxS Solid Solution

Abstract: We have systematically studied band bowing, band edges, and electronic properties of both zinc-blende and wurtzite Cd1–x Zn x S solid solutions by using a special quasirandom structures approach combined with hybrid DFT calculations. Hybrid DFT gives a more accurate description of the lattice constants, formation enthalpies, and electronic structures of the parent semiconductors than standard DFT. Alloying CdS with ZnS causes a downward band bowing that is dominated by volume deformation. The conduction- and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 62 publications
7
73
1
Order By: Relevance
“…7c. In particular, the Zn 0.5 Cd 0.5 S alloyed hollow nanospheres exhibited the best photocatalytic activities, which was in good agreement with the theorical calculation [36]. In addition, more than 95 % of RhB molecules in solution (15 mg/L) could be entirely decomposed in 40 min in presence of 10 mg Zn 0.5 Cd 0.5 S alloyed hollow nanospheres as shown in Fig.…”
Section: Optical Properties Of the Zn X Cd 1-x S Alloyed Hollow Nanossupporting
confidence: 86%
“…7c. In particular, the Zn 0.5 Cd 0.5 S alloyed hollow nanospheres exhibited the best photocatalytic activities, which was in good agreement with the theorical calculation [36]. In addition, more than 95 % of RhB molecules in solution (15 mg/L) could be entirely decomposed in 40 min in presence of 10 mg Zn 0.5 Cd 0.5 S alloyed hollow nanospheres as shown in Fig.…”
Section: Optical Properties Of the Zn X Cd 1-x S Alloyed Hollow Nanossupporting
confidence: 86%
“…Tuning its bandgap width and band-edge position by construction of Zn 1Àx Cd x S solid solutions is an efficient method to address these problems. [13][14][15][16] For example, our previous work confirmed that enhanced photocatalytic capabilities were achieved in Zn x Cd 1Àx S solid solutions (x = 0.1, 0.3, 0.5, 0.7, and 0.9) compared with pure ZnS and CdS photocatalysts, especially for x = 0.5, owing to the balance between the bandgap width and the position of the conduction-band edge. [17] On the other hand, fabrication of composites with graphene is also a promising way to enhance the photoactivity of traditional semiconductor photocatalysts.…”
Section: Introductionmentioning
confidence: 52%
“…In ZnSe/CdS interfacial alloying with a fast cation diffusion and a relatively slower anion diffusion leads to a region at the core with a composition close to Zn x Cd 1 − x Se and an inner shell composed of Zn 1 − x Cd x S. As the alloyed materials have band edges between those of the pure, binary compounds a potential trough at the valence band edge is formed in the sulfur-rich region that further confines the 1S hole to the core [28]. This effect can be enhanced by band bowing, which causes the band edges to change non-linear with composition x [41][42][43]. The effect is more pronounced when the gradient involves two anions.…”
Section: Impact Of Random Phase Mixingmentioning
confidence: 99%